2014
DOI: 10.1111/clr.12464
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes of dental implant therapy in a large randomly selected sample

Abstract: It is suggested that patient-perceived outcomes of implant-supported restorative therapy are related to (i) age and gender of the patient, (ii) the extent of restorative therapy and (iii) the clinician performing the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 20 publications
10
77
7
Order By: Relevance
“…Accordingly, it could be expected a higher number of noncompliant patients during follow‐up in an effectiveness study with many referral dentists as compared to small efficacy studies where the controls per se are important parts of the study protocol. In a recent effectiveness study it was reported that 81% of 4716 included patients in two different age groups answered a questionnaire, while only 66% of 900 selected patients in this group showed up for a later actual clinical examination . In another effectiveness study where altogether 184 patients were retrospectively included into a study group, based on earlier taken radiographs showing “progressive bone loss,” only 46% of them showed up later for a clinical examination to examine the health of the peri‐implant mucosa .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it could be expected a higher number of noncompliant patients during follow‐up in an effectiveness study with many referral dentists as compared to small efficacy studies where the controls per se are important parts of the study protocol. In a recent effectiveness study it was reported that 81% of 4716 included patients in two different age groups answered a questionnaire, while only 66% of 900 selected patients in this group showed up for a later actual clinical examination . In another effectiveness study where altogether 184 patients were retrospectively included into a study group, based on earlier taken radiographs showing “progressive bone loss,” only 46% of them showed up later for a clinical examination to examine the health of the peri‐implant mucosa .…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, in 2003, the federal subsidies for implant-supported restorative therapy increased for patients ≥65 y of age. A reference group of younger individuals (45-54 y) was also included in the study (Derks et al 2014). All data are given in percentages unless otherwise noted.…”
Section: Discussionmentioning
confidence: 99%
“…The patient material used in the present study has been previously described (Derks et al 2014). Briefly, 4,716 subjects in 2 age groups (45-54 y and 65-74 y in 2003) provided with implant-supported restorative therapy in 2003 were randomly selected from the national data register of the SSIA.…”
Section: Study Samplementioning
confidence: 99%
“…In another study with a follow‐up period of 6 years, peri‐implantitis was found in 13% of the participants (Konstantinidis, Kotsakis, Gerdes, & Walter, ). Over a longer perspective, others have found success rates of ~80% (Daubert et al., ; Derks, Håkansson, Wennström, Klinge, & Berglundh, ; Derks, Håkansson, Wennström, Tomasi, et al. ; Van Velzen et al., ).…”
Section: Discussionmentioning
confidence: 99%